Mycobacterium marinum hand infection: a case report and literature review - Liu, Chunping; Hao, Jiahao; Song, Minghui; Ye, Jiaqing; Zheng, Cuiying; Huang, Yinqi; Feng, Zhongjun; Jiang, Ruiping; Shi, Yan; Gao, Weili; Zuo, Huifen; Zhao, Zhenjun; et al. (Frontiers in Medicine, 2024)
Mycobacterium marinum, a photochromogenic, slow-growing mycobacterium, thrives in both marine and freshwater environments. Optimal growth occurs between 25°C and 35°C, with survival becoming challenging above 37°C. Typically, M. marinum enters the body via skin abrasions, often leading to infections of the upper extremities. Diagnosis of M. marinum infection is frequently challenging and delayed due to the difficult pathogen identification. At present, a standardized treatment protocol has yet to be established. Presented herein is a case study detailing an infection of the right hand's middle finger caused by M. marinum. Notably, his occupation as a chef, handling fish and seafood post-injury, was a significant factor. Histological examination of the skin biopsy and positive acid-fast staining were consistent with a diagnosis of mycobacterial infection. Pathological examination confirmed a skin infection with infectious granuloma, and tissue section acid-fast staining revealed acid-fast bacill. Cultures on Columbia blood agar yielded rough, flattened, yellow-fleshy colonies after 10 days, which was identified as M. marinum through 16S rRNA sequencing. The patient responded well to a 3-month regimen of oral moxifloxacin (0.4 qd) and linezolid (0.6 qd), resulting in rash resolution and pain relief, with no recurrence observed for 1-year follow-up. This report presents the first documented acid-fast staining images of M. marinum tissue sections and colony morphology photographs, offering an in-depth view of M. marinum's morphological characteristics. It aims to enhance awareness of M. marinum infections, underscore the necessity for clinicians to delve into patient histories, and provide a review of the clinical manifestations, diagnostic techniques, therapeutic approaches, and pathogenic mechanisms associated with M. marinum.